אברהם מלמט, מקורות לתולדות ישראל וארצו בתקופת המקרא. תאלף השני לפסה״נ Sources for Early Biblical History. The Second Millenium B.C. In Hebrew Translation (1964)
I. From the Land of Hebrew Origins. Akkadian Documents (Mari, Nuzi); II. Canaan before the Israelite Conquest. Egyptian Documents, Akkadian Documents (Taanach, el-Amarna, Alalakh, Ugarit); III. Canaan during the Israelite Conquest and Settlement. Egyptian Documents. International Treaties (Akkadian, Hittite, Egyptian). Assyrian Documents.